Effect of one week of CPAP treatment of obstructive sleep apnoea on 24‐hour profiles of glucose, insulin and counter‐regulatory hormones in type 2 diabetes. Issue 3 (12th December 2016) - Mokhlesi, Babak; Grimaldi, Daniela; Beccuti, Guglielmo; Van Cauter, Eve
Abstract : Studies examining the impact of CPAP treatment on glycaemic control have yielded conflicting results, partly because of insufficient nightly CPAP use. We examined the 24‐hour profiles of glucose, insulin and counter‐regulatory hormones in 12 subjects with type 2 diabetes and OSA before and after 1 week of effective in‐laboratory CPAP therapy over an entire 8‐hour night thus ensuring optimal CPAP compliance. Blood samples were collected every 15 to 30 minutes for 24 hours under controlled conditions. The 24‐hour mean glucose decreased from 153.2 ± 33.0 to 139.7 ± 24.2 mg/dL with CPAP (−13.5 ± 13.5 mg/dL; P = .005) without change in insulin levels. Morning fasting glucose levels decreased by 14.6 ± 3 mg/dL ( P = .001) and the dawn phenomenon decreased by 7.8 ± 9.8 mg/dL ( P = .019). CPAP treatment decreased norepinephrine levels while the 24‐hour profiles of growth hormone and cortisol remained unchanged. In conclusion, 1 week of effective treatment of OSA over an entire 8‐hour night results in a clinically significant improvement in glycaemic control via an amelioration of evening fasting glucose metabolism and a reduction in the dawn phenomenon, a late‐night glucose increase that is not adequately treated by oral medications. Clinical Trials Information :ClinicalTrials.gov Identifier: NCT01136785.